Baryon-number — flavor separation in the topological expansion of QCD - David Frenklakh; Dmitri Kharzeev; Giancarlo Rossi; Gabriele Veneziano (Journal of High Energy Physics)
Abstract Gauge invariance of QCD dictates the presence of string junctions in the wave functions of baryons. In high-energy inclusive processes, these baryon junctions have been predicted to induce the separation of the flows of baryon number and flavor. In this paper we describe this phenomenon using the analog-gas model of multiparticle production proposed long time ago by Feynman and Wilson and adapted here to accommodate the topological expansion in QCD. In this framework, duality arguments suggest the existence of two degenerate junction-antijunction glueball Regge trajectories of opposite C $$ \mathcal{C} $$ -parity with intercept close to 1/2. The corresponding results for the energy and rapidity dependence of baryon stopping are in reasonably good agreement with recent experimental findings from STAR and ALICE experiments. We show that accounting for correlations between the fragmenting strings further improves agreement with the data, and outline additional experimental tests of our picture at the existing (RHIC, LHC, JLab) and future (EIC) facilities.